Syariah Review of Online Buying and Selling Transactions on FaceBook - Malik, Dwiki Subchi; Hasan, Nur; Muhibban (PT Elaborium Elevasi Indonesia, 2025)
The development of digital technology has transformed buying and selling transaction patterns, one of which is through social media platforms like Facebook. Unlike formal marketplaces, transactions on Facebook generally occur informally and personally, without consumer protection systems or integrated payment mechanisms. This study aims to examine online buying and selling practices on Facebook from the perspective of Islamic law, focusing on the clarity of contracts, honesty in product information, and mutual consent between parties. This research uses a qualitative method with a descriptive-analytical approach. Data were obtained through interviews with business actors and active buyers on Facebook, as well as direct observation of transaction activities in several buy-and-sell groups. The findings show that most transactions do not fully comply with sharia principles, particularly in terms of information transparency and clarity of agreements. Nevertheless, there are also business actors who have consciously begun to apply the principles of Islamic commercial ethics. This study recommends the need for sharia education in informal online trade and the strengthening of Islamic business ethics in the digital realm.